MULTILINGUALISM IN ADVERTISING: A LINGUISTIC LANDSCAPE STUDY AT TIMOR PLAZA, DILI, TIMOR-LESTE - Martins, Agus; Gomes, Agalita (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Language use in public spaces reflects broader sociocultural dynamics, yet limited research has examined multilingual practices in commercial contexts in Timor-Leste. This study investigates the linguistic landscape (LL) of advertising signs at Timor Plaza in Dili, focusing on language distribution and the motivations behind language selection. The main objective of this study is to analyze how language choice in advertising signage reflects sociocultural interaction, identity negotiation, and power relations within a multilingual environment. Using a qualitative design, the research employed documentary analysis of 142 advertising signs, semi-structured interviews with shop owners and managers, and photographic documentation as data collection techniques. Data were analyzed thematically to identify linguistic patterns and communicative motivations. The analysis shows that English (44%) and Tetun (24%) dominate the signage, while bilingual combinations of Tetun and English account for 30%, and multilingual signs using Portuguese or Bahasa Indonesia represent only 2%. English is primarily employed to project modernity, cosmopolitanism, and global appeal, whereas Tetun ensures cultural relevance, authenticity, and accessibility for local audiences. The occasional inclusion of Portuguese and Bahasa Indonesia reflects Timor-Leste’s colonial history and regional connections, signifying both heritage and proximity. Overall, the linguistic landscape at Timor Plaza demonstrates a deliberate balance between globalization and local identity, positioning language as both a communicative and symbolic resource. This study advances theoretical understanding of linguistic landscapes by emphasizing the dynamic relationship between language, commerce, and identity, and it provides practical implications for language policy, marketing communication, and sociocultural planning in multilingual societies.